Rapid Dendritic Cell Activation and Resistance to Allotolerance Induction in Anti-CD154-Treated Mice Receiving CD47-Deficient Donor-Specific Transfusion. Issue 3 (April 2014) - Wang, Yuantao; Wang, Hui; Bronson, Roderick; Fu, Yaowen; Yang, Yong-Guang
CD47–SIRPα signaling plays an important role in regulating macrophage and dendritic cell (DC) activation. Here we investigated the role of CD47 expression on donor cells in tolerance induction by combined treatment with donor-specific transfusion (DST) plus anti-CD154 mAb in a mouse model of fully MHC-mismatched heart allotransplantation. The majority of BALB/c recipient mice that received anti-CD154 and CD47 +/+ B6 splenocytes (DST) showed indefinite donor heart survival (median survival time, MST > 150 days). Donor heart survival was improved in anti-CD154-treated BALB/c mice that received CD47 +/- (MST = 90 days) or CD47 -/- B6 DST (MST = 42 days) when compared to the nontreated (MST = 7 days) and anti-CD154 alone-treated (MST = 15 days) controls, but significantly reduced when compared to mice receiving anti-CD154 plus CD47 +/+ B6 DST. Recipient mice treated with anti-CD154 plus CD47 -/- or CD47 +/- DST also showed significantly increased antidonor, but not anti-third-party, MLR responses compared to those receiving anti-CD154 and CD47 +/+ DST. Furthermore, CD47 -/- DST induced rapid activation of CD11c hi SIRPα hi CD8α - DCs via a mechanism independent of donor alloantigens. These results demonstrated that CD47 expression on donor cells is essential to the success of tolerance induction by combined therapy with DST and CD40/CD154 blockade.